Confirmation of the efficacy of hepatic tissue iron index in differentiating genetic haemochromatosis from alcoholic liver disease complicated by alcoholic haemosiderosis. Issue 2 (February 1991) - Sallie, R W; Reed, W D; Shilkin, K B
Abstract : The hepatic tissue iron index proposed by Bassett et al was evaluated in 35 patients with homozygous genetic haemochromatosis, 67 patients with alcoholic liver disease, and 18 patients with other forms of chronic liver disease with and without cirrhosis. In patients with cirrhosis hepatic tissue iron concentration reliably differentiated alcoholic liver disease from genetic haemochromatosis. Although mean iron concentration was greater in patients with prefibrotic haemochromatosis than in those with prefibrotic alcoholic liver disease, some overlap occurred and complete differentiation of the two conditions was not possible. This overlap was particularly evident in some young patients with haemochromatosis in whom the tissue iron concentration grade fell in the range commonly seen in alcoholic haemosiderosis. Inability to differentiate early genetic haemochromatosis from alcoholic liver disease complicated by haemosiderosis was also a problem with standard Perls's staining. When the hepatic tissue iron index was calculated (hepatic tissue iron concentration/patient's age in years), clear differentiation of genetic haemochromatosis from both alcoholic liver disease and other forms of chronic liver disease was obtained in both cirrhotic and precirrhotic patients. This study confirms that the hepatic tissue iron index is a useful means of differentiating patients with genetic haemochromatosis from those with alcoholic liver disease. We suggest that biochemical estimation of tissue iron concentration and calculation of the tissue iron index in all patients in whom genetic haemochromatosis is a possible diagnosis will reduce the likelihood of misdiagnosing this as alcoholic liver disease.